Nanograined GeSe4 as a Thermal Insulation Material - Hao, Qing; Coleman, Garrett J.; Xu, Dongchao; Segal, Evan R.; Agee, Phillip; Wu, Shijie; Lucas, Pierre (Frontiers in Energy Research, 2018)
Owing to its amorphous structure, a chalcogenide glass exhibits a thermal conductivity k approaching the theoretical minimum of its composition, called the Einstein's limit. In this work, this limit is beaten in an amorphous solid consisting of glassy particles joined by nanosized contacts. When amorphous particles are sintered below the glass transition temperature under a high pressure, these particles can be mechanically bonded with a minimized interfacial thermal conductance. This reduces the effective k below the Einstein's limit while providing superior mechanical strength under a high pressure for thermal insulation applications under harsh environments. The lowest room-temperature k for the solid counterpart can be as low as 0.10 W/m∙K, which is significantly lower than k 0.2 W/m∙K for the bulk glass.